In Situ Derived Bi Alloys for High-Performance Li-Ion Batteries: Effect of Conversion Chemistry, Mesomatrix, and Electrolyte. Issue 8 (1st August 2022) - Ramirez, G.; Halajko, A.; Amatucci, G. G.
Abstract : Lix Bi alloys are a unique path to enable extraordinarily high rate, safer, and high volumetric energy density batteries. The effectiveness of BiF3 as an electrochemical precursor to a Lix Bi nanocomposite with excellent cycling efficiency extending beyond 250 cycles is explored to identify key factors critical to future successful development. The relationships between the converted crystallite size and subsequent electrochemical properties were reported with a specific focus on cycling efficiency. Through electrochemical and physical characterization of post-converted BiF3, Bi2 O3, and Bi2 S3, the size of the post-conversion Bi product was directly correlated with the ionic conductivity of the in situ formed Li salt matrix and subsequent cycling stability. Further key areas for development were introduced, including volumetrically dense conductive alternatives to C and electrolyte formulations, which demonstrate significant improvements in cycling stability. In addition, we demonstrate the ability of BiF3 -derived Lix Bi alloy thin films to delithiate with an 80% utilization at >100 C rate despite the presence of a LiF nanomatrix.